Assessing risk for recidivism in individuals convicted of stalking offenses: predictive validity of the guidelines for stalking assessment and management - Foellmi, Mélodie C. (Criminal justice and behavior, 2016)
This study examined the internal validity and predictive accuracy of the Guidelines for Stalking Assessment and Management (SAM), a structured professional judgment risk assessment tool for stalking. Interviewers rated 89 stalking offenders on the Psychopathy Checklist: Screening Version (PCL:SV) and SAM Nature (N) and Perpetrator (P) subscales. Researchers obtained stalking and violence outcomes prospectively from several sources, for an average follow-up period of 2.5 years. Cox Proportional Hazard analyses including SAM and PCL:SV scores demonstrated a significant positive relationship between SAM total and subscale scores in predicting stalking recidivism, whereas PCL:SV scores were negatively associated with recidivism. However, the SAM clinical risk ratings did not significantly predict stalking reoffending. There were also no significant associations between SAM scores and violent outcomes. These findings provide mixed support for the use of the SAM as a risk assessment tool for stalking offenders.